2007
DOI: 10.1002/hyp.6390
|View full text |Cite
|
Sign up to set email alerts
|

Chloride, hydrochemical and isotope methods of groundwater recharge estimation in eastern Mediterranean areas: a case study in Jordan

Abstract: Abstract:Jordan is classified as an arid to semi-arid country with a population according to 1999 estimates of 4Ð8 millions inhabitants and a growth rate of 3Ð4%. Efficient use of Jordan's scarce water is becoming increasingly important as the urban population grows. This study was carried out within the framework of the joint European Research project 'Groundwater recharge in the eastern Mediterranean' and describes a combined methodology for groundwater recharge estimation in Jordan, the chloride method, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…2) is 31.71 mm year -1 . This recharge rate, which represents 10.5% of the total rainfall, agrees with the results obtained in similar studies in Wadi Yalamlam basin and other adjacent basins in Saudi Arabia and other arid parts of the world (Allison 1988;Wood and Sanford 1995;Bazuhair and Wood 1996;Wood et al 1997;Wood 1999;Love et al 2000;Subyani 1997;Subyani and Bayumi 2001;Edmunds et al 2002;Subyani and Ş en 2006;Zagana et al 2007). …”
Section: Recharge Ratesupporting
confidence: 92%
“…2) is 31.71 mm year -1 . This recharge rate, which represents 10.5% of the total rainfall, agrees with the results obtained in similar studies in Wadi Yalamlam basin and other adjacent basins in Saudi Arabia and other arid parts of the world (Allison 1988;Wood and Sanford 1995;Bazuhair and Wood 1996;Wood et al 1997;Wood 1999;Love et al 2000;Subyani 1997;Subyani and Bayumi 2001;Edmunds et al 2002;Subyani and Ş en 2006;Zagana et al 2007). …”
Section: Recharge Ratesupporting
confidence: 92%
“…We observed even higher d‐excess values during winter for springs close to Beirut in the Lebanon Mountains (Koeniger et al , data not shown). Such high d‐excess values were reported earlier and explained by moisture recycling over the Mediterranean Sea (IAEA, , ; Gat, ; Gat and Carmi, ; Gat and Dansgaard, ; Gat et al ., ; Zagana et al ., ; Stadler et al ., ). For all spring samples, we observed a linear relationship between δ 18 O and d‐excess values as shown in Figure .…”
Section: Discussionmentioning
confidence: 97%
“…Delineation of recharge areas of karst springs, also referred as capture zones, is critically very important for protection of spring water resources (Abbott et al, 2000), especially in karst terrains where the aquifers are susceptible to a greater range of environmental impact problems (Ford and Williams, 2007). Because of various meteorological and physiographical effects, the meteoric water at a specific location has a characteristic isotopic signature (Gat, 1971;Clark and Fritz, 1997;Lee et al, 1999;Price and Swart, 2006) that serves as a basis for delineating the recharge areas of groundwater/spring water (Fontes et al, 1967;Gonfiantini et al, 1976;Zagana et al, 2007;Jeelani et al, 2010) and for understanding the components and mechanism of groundwater recharge (Clark and Fritz, 1997;Mook, 2006). Stable isotopes of oxygen (δ 18 O) and hydrogen (δ 2 H) have been widely used as a conservative groundwater tracer to identify the recharge areas (Clark and Fritz, 1997).…”
Section: Introductionmentioning
confidence: 99%